Research Progress in Active Ingredients of Chrysanthemum and Its Application in Health Foods for Relieving Visual Fatigue in China - LIU Gaigai, DUAN Hao, YANG Tianyu, YAN Wenjie (Shipin Kexue, 2025)
The increasing frequency of people using electronic products has led to an increase in the amount of time spent with the eyes, which in turn often results in a variety of eye discomforts such as soreness, dryness and blurriness, a condition known as visual fatigue. A growing body of studies suggest that visual fatigue can be effectively alleviated through dietary supplementation, particularly through supplementation of substances with both medicinal and culinary uses. At present, there are more and more health food products for relieving visual fatigue and improving eyesight available on the market, which indicates that those products are in great demand and has a good development prospect. Chrysanthemum, as one of the main ingredients of visual fatigue-relieving health foods, can effectively reduce visual fatigue caused by oxidative stress and inflammatory damage. This article analyzes the differences in the chemical structures and contents of antioxidant and anti-inflammatory components in different varieties of chrysanthemum. Through the national special food information query platform under the State Administration for Market Supervision, health food products containing chrysanthemum are summarized and analyzed. Moreover, we review recent progress in research on the safety of chrysanthemum and its application in relieving visual fatigue. We also put forward opinions and outlooks on future research with a view to providing a reference and theoretical foundation for the development of visual fatigue-relieving health foods mainly based on chrysanthemum in the future.